Improving Mastery of Basic English Vocabulary Through Multiple-Choice Questions at MDTA AL WASHLIYAH: A Classroom Action Research Study" (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2024)
This study aims to improve the mastery of basic English vocabulary through the use of multiple-choice questions at MDTA AL WASHLIYAH. The research is conducted in the form of Classroom Action Research (CAR) with fifth-grade students as the subjects. The method used involves a cycle of planning, implementation, observation, and reflection. At the initial stage, the researcher identifies students' difficulties in understanding basic English vocabulary. Then, the researcher designs and implements a series of learning activities based on multiple-choice questions intended to strengthen vocabulary comprehension. Data is collected through pre-tests and post-tests as well as classroom observations. The analysis results show a significant improvement in students' mastery of basic vocabulary after applying this strategy. The study concludes that the use of multiple-choice questions can be effective in enhancing basic English vocabulary mastery among students at MDTA AL WASHLIYAH and recommends the implementation of this method in English language teaching practices at the elementary level.